OPTIMALISASI KINERJA ANGGOTA SATLANTAS POLRES JEPARA - Andi M. Indra Waspada (Jurnal Ekonomi dan Bisnis, 2015)
This study aimed to test the performance improvement model with variables: organizational climate, work motivation, communication, job satisfaction, and trust. The study was conducted by survey method by distributing questionnaires to 105 members of the â€œSatlantas Polres Jeparaâ€. Sampling studies using Random Sampling Proportional method.The results showed that the performance of members can be optimized by building a conducive organizational climate, as evident in this study that organizational climate directly affects the performance. Next the performance of members can also be optimized by always providing the motivation and confidence to members, because this study also proved that both these variables directly affect performance. Furthermore, this study also prove that job satisfaction as an intervening for the relationship of organizational climate to performance, can be interpreted that in order to optimize the performance of effective communication can be built, but prior to the performance improvement should be created in the working member satisfaction first.Keywords: organizational climate, work motivation, communication, trust, job satisfaction, performance